La música renacentista como una etapa de la evolución continua del tonalismo (2015)
In this project we sought to help establish whether Renaissance music (XV and XVI centuries), considered "modal", is substantially different from "tonal" music of later centuries or if, rather, it is the same tonal system that It evolved over time. For this, we analyze (tilde by diacrisis of the past) a representative group of works of the time, with special emphasis on the problem of harmonic functionality as an expression of syntactic differentiation but we also use other specific analytical criteria and qualitative methods such as Quantitative Our search, rather than fighting with the state of the matter at present according to the authorized writers, tried to refine and gather their theoretical results and ours in conclusions with a more generalizing and synthetic theorizing vision. There is a fundamental aspect, although collateral for the subject that concerns us here, that our research group has been examining for years in the projects already completed and that of the musical lexicon, an issue that we have considered a priority in musical theorization as a branch of musicology, given the denotative and explanatory power that is expected of him, as in any scientific field and, on the other hand, the little rigor with which it has been used, at least in part and not only in the musicological writings in the Castilian language. Let us revise, then, terms such as tonality, functionality, modalism, subjectivity, compass and metric, variety (varietas) and harmony in relation to the counterpoint.